Estimation of the Amino Acids of Protein from the Seeds of Kigelia pinnata DC - Sampurna, T.; Siva Sankara Rao, T. (Asian Journal of Chemistry, 2010)
The protein extracted from the defatted seeds of Kigelia pinnata DC on hydrolysis gave the amino acids which were identified by chromatographic techniques. Each amino acid of the protein was quantitatively estimated by measuring the optical density with the aid of a spectrophotometer.